2008
DOI: 10.1007/s00284-007-9086-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Plant Growth–Promoting Traits of Bacteria Isolated from Larval Guts of Diamondback Moth Plutella xylostella (Lepidoptera: Plutellidae)

Abstract: Eight bacterial isolates from the larval guts of Diamondback moths (Plutella xylostella) were tested for their plant growth-promoting (PGP) traits and effects on early plant growth. All of the strains tested positive for nitrogen fixation and indole 3-acetic acid (IAA) and salicylic acid production but negative for hydrogen cyanide and pectinase production. In addition, five of the isolates exhibited significant levels of tricalcium phosphate and zinc oxide solubilization; six isolates were able to oxidize sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(87 citation statements)
references
References 31 publications
3
80
0
4
Order By: Relevance
“…These results were consistent with earlier report on the P and Zn solubilizing properties of Acinetobacter sp. [44]. Nearly all the Acinetobacter species isolated from rhizosphere soil of the three wheat varieties in the present study were efficient phosphate and zinc solubilizers and produced iron chelating siderophores [45].…”
Section: Phosphate Solubilization and Mineralizationmentioning
confidence: 94%
“…These results were consistent with earlier report on the P and Zn solubilizing properties of Acinetobacter sp. [44]. Nearly all the Acinetobacter species isolated from rhizosphere soil of the three wheat varieties in the present study were efficient phosphate and zinc solubilizers and produced iron chelating siderophores [45].…”
Section: Phosphate Solubilization and Mineralizationmentioning
confidence: 94%
“…SW5 Acinetobacter spp. are widely distributed in soil and water, and some of them have been reported to enhance the growth of many plants (Indiragandhi et al, 2008;Gulati et al, 2009;Shi et al, 2011). In this study Acinetobacter sp.…”
Section: Resultsmentioning
confidence: 99%
“…(Huddedar et al, 2002;Chaiharn et al, 2008;Rokhbakhsh-Zamin et al, 2011). Although many species of Acinetobacter are reported as PGPR (Indiragandhi et al, 2008;Gulati et al, 2009;Kang et al, 2009;Shi et al, 2011), this SW5 strain showed a high plant growth promoting capability. SW5 strain has a 97.875% of sequence homology of 16S rRNA gene compared with the type strain A. guillouiae ATCC 11171 T reported recently by Nemec et al (2010), and some general characteristics of SW5 strain were coincided with those of other Acinetobacter spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…helps in disease suppression (Indiragandhi et al, 2008). IAA helps the host plants to stimulate seed germination, root formation and root elongation (Ahemad and Kibret, 2014) whereas HCN was also reported to help in disease suppression (Haas et al, 1991).…”
Section: A) B)mentioning
confidence: 99%